Sosialisasi Penjernihan Air Baku Dengan Menggunakan Elektrokoagulasi Di SMP & SMA Dr. Wahidin Sudirohusodo - Harlem Marpaung; Rikson Siburian; Crystina Simanjuntak (UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2018)
This Research has been done in one of Junior and Senior High Schools of Dr. Wahidin Sudirohusodo by using water samples at the site for iron absorption by electrolysis method using aluminum electrode. By using visible spectrophotometer and standard solution of FeCl3.6H2O series can be obtained iron content before eletrolisis, ie 1 = 2.5548 mg / L and sample 2 = 1.4458 mg / L. After electrolysis and measured iron content using visible spectrophotometry and standard solution of FeCl3.6H2O series, iron absorption results obtained in sample 1 were 44.90% and in sample 2 were 21.84%.